2022
DOI: 10.1002/batt.202200059
|View full text |Cite
|
Sign up to set email alerts
|

Strategies towards High Performance Lithium‐Sulfur Batteries

Abstract: Batteries & Supercaps www.batteries-supercaps.org Review doi.org/10.1002/batt.202200059 of LSBs. In this review, the working principles and challenges of LSBs are briefly introduced. The strategies to overcome the challenges of LSBs, such as electrode design and modification, development of novel electrolytes, separator modification/functional interlayer insertion, and protection of lithium anode are systematically discussed. The advanced in situ/operando characterization techniques deployed to reveal the redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 266 publications
1
29
0
Order By: Relevance
“…In general, extensive studies showed that HSSEs have excellent compatibility with oxide‐based cathode materials. Nevertheless, fundamental interfacial stability and compatibility with materials other than oxide cathode materials, such as Li 2 S or sulfur‐type cathode materials, [ 162 ] need to be investigated experimentally and theoretically.…”
Section: Electrochemical Stability Of Hssementioning
confidence: 99%
“…In general, extensive studies showed that HSSEs have excellent compatibility with oxide‐based cathode materials. Nevertheless, fundamental interfacial stability and compatibility with materials other than oxide cathode materials, such as Li 2 S or sulfur‐type cathode materials, [ 162 ] need to be investigated experimentally and theoretically.…”
Section: Electrochemical Stability Of Hssementioning
confidence: 99%
“…Significant volume change of S during the cycling process also causes mechanical cracking and poor electrical connectivity with the conductive substrate and electrode . Moreover, the uncontrolled growth of dendrites due to the uneven deposition of Li + ions on the surface of Li anodes causes detrimental effects such as the evolution of dead Li and the formation of unstable solid–electrolyte interphase (SEI) layer, increased polarization, and safety concerns for the Li–S batteries. Last, the shuttle effect caused by the dissolution of intermediate Li polysulfides in the electrolyte leads to irreversible S loss and, thus, a lower discharge capacity and Coulombic efficiency (CE). …”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to mitigating the shuttle effect of LiPSs, such as the construction of heterostructured materials in the cathode and the adoption of an advanced electrolyte. Weret et al explored the mechanism of a sulfurized polyacrylonitrile compound cathode and deciphered polysulfide dissolution and the shuttling effect . Besides, the trithiocyanuric acid was introduced into polyacrylonitrile by an electrospinning technique and further treated by inverse vulcanization to increase the sulfur content in the sulfurized polyacrylonitrile .…”
Section: Introductionmentioning
confidence: 99%